2010
DOI: 10.2135/cropsci2008.12.0720
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Catechins Applied to Susceptible Hosts Inhibit Parasitic Plant Attachment Success

Abstract: Parasitic plants utilize cell wall degrading enzymes (CWDEs) to penetrate their host plant and attach to host vasculature. Inhibition of CWDEs may confer resistance on susceptible hosts, offering a strategy for parasitic plant control. Here, exogenous application of green tea catechins, which inhibit pectin methylesterase (a CWDE), was used to delay parasitic plant attachment. Texas bluebonnet (Lupinus texensis Hook.) was grown with its naturally occurring root hemiparasite, Texas paintbrush (Castilleja indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Immunogold labeling of PME showed that this enzyme accumulates at the cell wall and Golgi apparatus of Orobanche cumana intrusive cells ( Losner-Goshen et al, 1998 ). PME may have a crucial role in parasitism since application of catechin, a PME inhibitor, results in reduced attachment of the facultative root parasite Castilleja indivisa to its host and has a similar effect on the stem parasite Cuscuta pentagona on Arabidopsis ( Lewis et al, 2010 , 2008 ). Pectin de-esterification by PME is a prerequisite for pectin degradation by polygalacturonase and pectate lyase.…”
Section: Cell Wall Modifications By Parasitic Plantsmentioning
confidence: 99%
“…Immunogold labeling of PME showed that this enzyme accumulates at the cell wall and Golgi apparatus of Orobanche cumana intrusive cells ( Losner-Goshen et al, 1998 ). PME may have a crucial role in parasitism since application of catechin, a PME inhibitor, results in reduced attachment of the facultative root parasite Castilleja indivisa to its host and has a similar effect on the stem parasite Cuscuta pentagona on Arabidopsis ( Lewis et al, 2010 , 2008 ). Pectin de-esterification by PME is a prerequisite for pectin degradation by polygalacturonase and pectate lyase.…”
Section: Cell Wall Modifications By Parasitic Plantsmentioning
confidence: 99%
“…By decreasing strigolactone production, they stimulate germination of nearby seeds less and can inhibit haustorium initiation (Echevarria-Zomeno et al 2006;Gobena et al 2017). If seeds germinate and reach a root, host plants can modify the cell walls of their roots to block haustorium penetration (Yoshida and Shirasu 2009;Lewis et al 2010). For example, the hypersensitive response in tomato prevents infestation by Cuscuta reflexa, an epiphytic Convolvulaceae, by restructuring the tomato cell wall (Lee and Jernstedt 2013).…”
Section: Plant Defense Reactionsmentioning
confidence: 99%